Applicability of CSP solar fields to the dry cooling of related thermodynamic cycles. (25th December 2017) - Espargilliere, H.; del Campo, L.; Echegut, P.; Py, X.; Muselli, M.; Rochier, D.
Highlights: The spectral infrared emissivity of CSP reflectors have been characterized. Aluminum films present higher performances than glass or aluminum mirrors. The fouling induced by outdoors conditions increases the IR radiative emissivity. The CSP solar field can be used as macro-heat-exchanger for dry cooling. Abstract: Concentrating Solar Power (CSP) technologies in arid areas suffer of a too high water consumption at the condenser of their power-block. The different alternative dry cooling technologies previously proposed to overcome this weakness lead to a decrease of 3–7% in whole efficiency of the power plant and a corresponding increase of 10% in the cost of the produced electricity. The new dry cooling approach proposed in the present study is based on using the solar field (SF) as a macro heat exchanger. Nightly, the extended available surface area of the SF allows convective thermal exchange with the surrounding environment and additional radiative heat transfer with the 3 K extra atmospheric space through the atmospheric window in between 8 and 14 µm. The exchanged radiative heat flow density depends directly on the optical properties of the exposed materials. In the present paper, performances of conventional and innovating reflective materials are presented through the assessment of their spectral emissivity. Aluminum film (innovating material) appears to be the most efficient one with a mean spectral emissivity around 95%, while glass mirrors (conventional materials) area round 86%. Moreover, within the spectral range of the atmospheric window 8–14 µm, aluminum film is more stable than the glass mirror with a respective standard deviation of 3 and 7.8 respectively. The results confirm that radiative heat transfer can contribute to the cooling needs of linear Fresnel and parabolic trough CSP plant power block at a level of 95% and 53% respectively.